Fruit growth characterization of the tomato (Solanum lycopersicum L.) hybrid ‘Ichiban’ grown under cover (2016)
The tomato (Solanum lycopersicum L.) is one of the more important crops that are consumed worldwide. In Colombia, the department of Boyaca is characterized as being the biggest producer of tomatoes, with production centered in the municipalities of Sutamarchan, Sachica, Santa Sofia and Villa de Leyva, where different cultivars and hybrids are produced that present different physiological behaviors, resulting in changes in conventional agronomic management. This study aimed to evaluate the growth and development of fruits from the tomato hybrid Ichiban under greenhouse conditions. This study evaluated the parameters of polar and equatorial diameters, diameter ratio, fresh mass and dry mass, and absolute and relative growth rates. The results were subjected to a descriptive analysis. Furthermore, the growth model was determined. The Ichiban hybrid had a simple sigmoid behavior, common in fleshy fruits, while the fresh mass and dry mass were fitted to a logistic, nonlinear model. Anthesis was seen at 50 days after transplant and the fruits reached physiological maturity 49 days after anthesis; during this period, 510.2 heating degree-days were accumulated. All of the variables presented significant differences (P≤0.01) and coefficients of determination above 0.9, indicating that the models are suitable for explaining the studied biological phenomena.